IMPLEMENTATION OF ACTIVITY BASED COSTING (ABC) SYSTEM TO DETERMINE THE COST OF GOODS MANUFACTURED (Case Study at PG. Kebon Agung Malang) - Farah Oliviatie (Fakultas Ilmu Administrasi Universitas Brawijaya, 2013)
This research aims to clarify the calculation of the cost of traditional accounting in determining cost of goods manufactured and explains the application of the calculation of Activity Based Costing System (ABC system) in determining cost of goods manufactured and differences in the calculation of cost of goods manufactured based on traditional cost accounting and calculation of the ABC system. Data collection technique is documentary with secondary data as a source of data. Data analysis was carried out in three stages are analyze the cost of goods manufactured PG. Kebon Agung Malang by the traditional cost accounting methods, calculation the cost of goods manufactured with the ABC system, compare the results of calculation of the cost of goods manufactured between the ABC traditional cost accounting systems. Based on the results of the first analysis in traditional cost accounting calculation in determining cost of goods manufactured showed that the sugar product Rp. 267,289,500,697, a molasses product Rp. 112,109,106,505. The second analysis results in the calculation of Activity Based Costing System (ABC system) in determining cost of goods manufactured showed that the sugar product Rp. 266,794,777,272, molasses product Rp. 111,873,541,769. A third analysis results show the difference obtained in traditional cost accounting calculation with calculation of the ABC system on sugar product Rp. 494,723,425 (overcosted), Molasses product Rp. 235,564,736 (overcosted). Keywords: Traditional Cost Accounting, Activity Based Costing System, Cost Of Goods Manufactured.